The impact of relational capital on supplier quality integration and operational performance. (18th August 2019) - Yu, Yubing; Huo, Baofeng
Abstract : This study explores the relationship between relational capital, supplier quality integration (SQI), and operational performance. We develop a model specifying the relationships between relational capital, SQI, quality orientation, and operational performance, which we test using data collected from 308 manufacturing companies in China. The results indicate that relational capital has a positive effect on operational performance and that SQI plays a full mediating role in their relationship. In addition, quality orientation positively affects the relationship between relational capital and SQI. The findings reveal how relational capital is related to operational performance theoretically and provide important managerial insights for supply chain quality managers to improve operational performance through SQI. The limitations of the study and future research directions are also discussed.